Enoch from Antiquity to the Middle Ages, Volume I Sources from Judaism, Christianity, and Islam - Reeves, John C.; Reed, Annette Yoshiko 1973- (Oxford Oxford University Press USA - OSO, 2018)
This volume provides a comprehensive set of core references to '1 Enoch'. It shows that the rich afterlives of Enochic texts and traditions can be studied more thoroughly by scholars of Second Temple Judaism and early Christianity as well as by scholars of late antique and medieval religions.
Cover -- Enoch from Antiquity to the Middle Ages, Volume I: Sources from Judaism, Christianity, and Islam -- Copyright -- Preface -- Contents -- Introduction -- Recovering the Enochic Library -- Tradition and Transmission -- Historical and Cultural Contexts -- 1. Stock Epithets and Cross-Cultural Cognomens -- Epithets "Seventh" -- "Righteous" -- "Scribe of Righteousness" -- "The Lord's Messiah" -- "Portraits" of Enoch -- 2. Enoch as Culture Hero: What Enoch Discovered, Learned, Taught, and Wrote -- Enoch 's Curriculum Vitae -- Enoch as Purveyor of Star-Lore and Calendar Reckoning -- Enoch as Savant of Cosmological Arcana -- Enoch as Inventor of Writing or Contributor to Book Culture -- Enoch as Haberdasher -- Weights and Measures -- Medical Lore -- 3. Enoch's Roles in Human Society -- Enoch as Teacher -- Enoch as Prophet -- Enoch as Authority on Religion and Its Practices -- Enoch as Ruler/Lawgiver -- Enoch as Builder -- Enoch as Warior -- Enoch as Legatee of Yared -- Enoch as Hermit -- Enoch as Sorcerer's Apprentice -- Enoch as Funeral Director -- 4. Enoch's Interactions with Angels -- Enoch as a Confidant and Apprentice of Angels -- Enoch Wields Angel-Like Power -- Enoch Bears Witness against the Watchers -- Enoch/Metatron/Idrīs Mediates betwen Heaven and Displaced Angels -- Enoch/Idrīs and the Angel of the Sun -- Enoch Encounters the Angel of Death -- Excursus: Ma'aseh R. Joshua b. Levi and Enochic Lore -- 5. Enoch's Escape from Death -- Enoch Is Taken Alive to Gan Eden or the (Eastern?) Ends of the Earth -- Enoch Is Taken Alive to Heaven/Paradise -- Enoch/Idrīs Is Raised to the Fourth Heaven -- Enoch/Idrīs/Metatron Is Raised to the Sixth Heaven -- Enoch/Hermes/Idrīs/Metatron Is Raised to the Seventh Heaven -- Enoch Serves There as Witness or Recording Scribe -- Enoch Administers Celestial Treasuries and Storehouses.
Description based on publisher supplied metadata and other sources
Keywords: Enoch-(Biblical figure); Ethiopic book of Enoch; Electronic books